UNACCOUNTED FACTORS OF PEDAGOGIC MOTOR ACTIVITY AND SEARCH OF PERSPECTIVES IN PHYSICAL EDUCATION OF STUDENTS AT MODERN SOCIETY - Вржесневський, І. І. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
Search the prospects of development of physical education students in today’s changing society inevitably leads to the subject of theoretical reflection and revision of some dogmatic systems in motor activity of man. We propose for the consideration of some unaccounted factors having a negative impact on the efficiency of physical education students. All these factors combine two things: disregard their influence in the modern theory and methodology of physical culture; the need to use coercion and self-constraint for overcoming them. The article raised the question of the need for scientific evidence and organizing traditionally ignored factors – laziness; fears of people in the context of individual physical effort; shame for his physical imperfections; cognitive dissonance in a generalized perception of physical activity